bahasa inggris - Iflatul Mus’ifah; Naila Rahma Mufida; Fatma Azzahra Nur’aini (Journal of Public Policy Analys, 2024)
Mathematics cards are one of the products produced by a company called "EDUPROPS" which operates in the field of providing educational teaching aids for school children. ExShapes math cards are a series of cards that combine flat shapes with exponent numbers. The research focuses on market research needs for ExShapes math card products, so that the product's marketing potential can be identified more clearly. The analysis method was carried out using trend analysis, similarity, contradictions, and odd groupings on primary data that had been obtained through distributing questionnaires. The final result of the research is the results of the respondents' trend analysis regarding respondents' interest in ExShapes math cards based on the gender and profession of each respondent, then their source of knowledge of math cards and the respondent's experience in using or playing math cards. In the similarity analysis, there was respondents' interest in buying mathematics cards in terms of design, price, quality or brand. The results of the contradiction analysis are the respondent's interest in the product and the results of the odd grouping analysis are that the respondent will promote the ExShapes math card product to other potential customers